Genetic diversity and selection of high-yielding genotypes from the Amazonian hevea germplasm for utilisation in rubber breeding programme - Ahmad Fauzi, Mohd Adi Faiz (2021)
Systematic initiatives in evaluation of Hevea germplasm are imperative in the development of improved cultivars with desirable characters. The main objective of the present study was to evaluate genetic diversity of the Amazonian Hevea germplasm in efforts to establish a breeding population consisting of selected genotypes with desirable traits for their utilisation in future rubber breeding programme. A total of 4,545 wild Hevea brasiliensis genotypes from eight Amazonas and Para populations, constituted the base materials for the present study. Evaluation on genetic diversity revealed significant variations in latex yield and vegetative traits among the genotypes. Majority of the wild genotypes produced considerably low amount of latex yield. Higher phenotypic coefficient of variations was observed for all traits compared to genotypic coefficient of variations, suggesting major effects of environmental factors on the expression of vegetative and yield traits. Latex yield recorded the highest magnitude of heritability and genetic advance, indicating that selection of genotypes based on this trait would give good selection response. The highest genetic distance was recorded between G95_MA and G95_ADN populations, while the lowest was between G95_BC and G95_ADN populations. Cluster analysis based on quantitative traits divided the eight populations into three clusters. The first two components in the principal component analysis accounted for approximately 86.90% of total variations. A total of 505 potential genotypes with desired characteristic were initially selected using multiple traits selection index and the relationship between latex yield, and morphological and bark structural traits were further evaluated. Latex yield showed significant and positive phenotypic correlations with plant girth, total number of latex vessel rings, total bark thickness and total leaf area. Plant girth recorded the highest direct positive effects on latex yield advocating its use as an indirect selection criterion towards increasing yield. Based on the principal component scores, Shannon-Weaver diversity index and Gower metric coefficient, a total of 128 genotypes were included in the final core collection. Furthermore, 78 genotypes were evaluated for resistance to two virulent isolates of Corynespora cassiicola (isolates CSB 16 and CLN 16) under both laboratory and greenhouse conditions. Significant differences were observed. Three genotypes had high level of resistance to both isolates in both conditions which could serve as good source of materials in breeding programmes. Results of the study present the genetic potential of the Amazonian Hevea germplasm for utilisation in future development of superior latex timber clones.